Quality of Public Services at the Social Security Agency of Health (Badan Penyelenggara Jaminan Sosial) Manpower Banjarmasin Branch Office - Suparjo; Riky Welli Saputra; Irawanto (East Asian Journal of Multidisciplinary Research, 2022)
The study aimed to analyze the quality of public services at the Banjarmasin Branch Office of Employment BPJS (Social Security Agency of Health). The research method used by the researcher is a descriptive analysis method. Observation, interviews, and documentation carried out the data collection techniques in this study. The data analysis technique used in this research is qualitative. The results of the study show (1) The accuracy of the services provided by employees is good enough in explaining matters related to participant requirements, making participant cards, claiming processes, and other public service activities organized by BPJS Ketenagakerjaan, although often when performing public services outside the office the community asks the same questions over and over again, the employees still give good explanations, (2) The speed of service in overcoming problems that occur in public services is quite good, it is just that the number of employees when performing public services outside the office is quite good. Can reduce the level of community satisfaction, and (3) Hospitality is good with employees who are always ready to help the community's needs in the public service process.